Recurrent and transformation of borderline to malignant phyllodes tumour with osteoid differentiation: a case report and literature review - Balachandran, Navin Raj; Abdullah, Norlia; Ismail, Muhammad Ishamuddin; Wong, Yin Ping; Azmi, Mohd Imree (Frontiers in Oncology, 2024)
This is an interesting case report of a breast malignancy in a young woman She was diagnosed to have an intermediate phylloides tumour despite her age. .It is rare for a young woman to have a recurrent and transformation of benign to malignant phyllodes tumour. This case also describes the unusual occurrence of malignant phylloides with axillary metastasis and osteoid differentiation. We feel that this case report will be able to provide useful and novel information to the pathological, surgical and oncological fraternity.